Analisis Kerapatan Vegetasi Untuk Kawasan Ruang Terbuka Hijau Tahun 2015-2020 Di Kota Bengkulu - Sihite, Hana Pebrina; Yulfa, Arie (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
The purpose of this study was to determine the vegetation density, availability of green open space, and changes in vegetation density for green open space in Bengkulu City in 2015 and 2022. The method used in this study applied NDVI analysis. The results of the study show that: (1) Based on the land area of ​​​​vegetation density in Bengkulu City in 2015 the vegetation density was dominated by medium density which had an area of ​​5,613.35 ha (42.41%). In 2022 the vegetation density is dominated by low density with an area of ​​4,580.45 ha (34.61%). (2) The availability of green open space in 2015 was 8,574 ha and in 2022 it was 8,299 ha. (3) Changes in the area of ​​vegetation density for green open spaces from 2015 to 2020 decreased by 767 ha. (4) The results of the NDVI accuracy test with the Confusion Matrix technique, obtained an accuracy of 80%, there has been a reduction in information due to cloud cover in 2022.